Sulfur Isotope Effects of Dissimilatory Sulfite Reductase - Leavitt, William D.; Bradley, Alexander S.; Santos, André A.; Pereira, Inês A. C.; Johnston, David T. (Frontiers in Microbiology, 2015)
The precise interpretation of environmental sulfur isotope records requires a quantitative understanding of the biochemical controls on sulfur isotope fractionation by the principle isotope-fractionating process within the S cycle, microbial sulfate reduction (MSR). Here we provide the only direct observation of the major (34S/32S) and minor (33S/32S, 36S/32S) sulfur isotope fractionations imparted by a central enzyme in the energy metabolism of sulfate reducers, dissimilatory sulfite reductase (DsrAB). Results from in vitro sulfite reduction experiments allow us to calculate the in vitro DsrAB isotope effect in 34S/32S (hereafter, 34εDsrAB) to be 15.3±2‰, 2σ. The accompanying minor isotope effect in 33S, described as 33λDsrAB, is calculated to be 0.5150±0.0012, 2σ. These observations facilitate a rigorous evaluation of the isotopic fractionation associated with the dissimilatory MSR pathway, as well as of the environmental variables that govern the overall magnitude of fractionation by natural communities of sulfate reducers. The isotope effect induced by DsrAB upon sulfite reduction is a factor of 0.3 to 0.6 times prior indirect estimates, which have ranged from 25 to 53‰ in 34εDsrAB. The minor isotope fractionation observed from DsrAB is consistent with a kinetic or equilibrium effect. Our in vitro constraints on the magnitude of 34εDsrAB is similar to the median value of experimental observations compiled from all known published work, where 34εr-p = 16.1‰ (r – p indicates reactant versus product, n = 648). This value closely matches those of MSR operating at high sulfate reduction rates in both laboratory chemostat experiments (34εSO4-H2S = 17.3±1.5‰) and in modern marine sediments (34εSO4-H2S = 17.3±3.8‰). Targeting the direct isotopic consequences of a specific enzymatic processes is a fundamental step toward a biochemical foundation for reinterpreting the biogeochemical and geobiological sulfur isotope records in modern and ancient environments.